Metodologia participativa aplicada ao manejo da zona de amortecimento das Estações Ecológica e Experimental de Itirapina, SP - Dutra-Lutgens, Helena (Universidade Federal de São Carlos, 2010)
Protected Areas represent a fundamental strategy for biodiversity conservation, yet it is essential to consider the inclusion of each in its regional context. The support and participation of society are very important to the conservation of these areas, especially with regard to their buffer zones. The aim of the present study was to develop a proposal for limits and management for the buffer zone of Itirapina protected areas, according to technical parameters and with the participation and integration of various groups of social actors, to support its effective implementation and maintenance of social and environmental functions provided by it. The research was based on the methodological principles of action research and was conducted in three stages:in the first of them was performed a dynamic analysis of the use and occupation of land in the study area and identification of groups of social actors from around the Itirapina protected areas; the second stage examined through semistructured qualitative interviews, the meaning of Itirapina protected areas and the role of the buffer zone from the perspective of groups of social actors from around these areas. The third stage brought together the people interviewed in the second step, in a planning workshop for a proposed definition of boundaries and zoning for the buffer zone of Itirapina protected areas.The surrounding population identified the goods and services provided by natural ecosystems, related them to the maintenance of environmental functions with the presence of protected areas in the region, reported changes in environmental functions due to human activities in the surrounding, and also are able to participate in decision-making processes that involve the protected areas and its buffer zone.
Keywords: Unidades de conservação; Zona de amortecimento; Planejamento participativo; Área protegida; Serviços do ecossistema; Unidades de conservação; Buffer zone; Participatory planning; Protected areas; Ecosystem services; CIENCIAS BIOLOGICAS::ECOLOGIA